Pension Reform and the Development of Pension Systems : An Evaluation of World Bank Assistance - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This report analyzes the Bank's assistance to support pension reform to determine if the Bank's strategy was relevant and if it was followed. The evaluation assesses whether pension reform decisions reflected best practice guidelines at entry, and whether Bank-assisted reforms achieved their social, macroeconomic, and financial objectives. The report also evaluates the Bank's assistance in building institutional capacity, coordinating within the Bank, and cooperating with other international organizations. Finally, the evaluation summarizes these findings and presents specific recommendations for the future.